2022
DOI: 10.3390/ijerph19127155
|View full text |Cite
|
Sign up to set email alerts
|

Financial Support for Agriculture, Chemical Fertilizer Use, and Carbon Emissions from Agricultural Production in China

Abstract: In the past 15 years, China has emitted the most carbon dioxide globally. The overuse of chemical fertilizer is an essential reason for agricultural carbon emissions. In recent years, China has paid more and more attention to financial support for agriculture. Therefore, understanding the relationship between chemical fertilizer use, financial support for agriculture, and agricultural carbon emissions will benefit sustainable agricultural production. To achieve the goal of our research, we selected the panel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…The essence of the urbanization process is a multidimensional transmutation process accompanied by the flow of capital, labor, technology, and other factors from the countryside to the city, and the reconfiguration of factors between urban and rural areas, which has a great impact on the production scale and cultivation structure of agriculture (Tian et al, 2016;Xiong et al, 2020;Joséf, 2022); 4) rural labor education level differences (ED) is expressed by the average years of education of rural residents. The labor force is the decision maker of agricultural production methods and its level of education has a significant impact on the adoption and application of pioneering technologies (Wang et al, 2019;Wu et al, 2021;Khanh and Nguyen, 2022); 5) financial development level differences (FI) is expressed by the ratio of deposit and loan balance of financial institutions to GDP, a sound financial service system can provide financial support for agricultural transformation and upgrading and green technology progress (Huang et al, 2014;Cao et al, 2022;Gao et al, 2022); 6) agricultural irrigation water utilization rate differences (WA) is expressed by the ratio of effective irrigated area to cultivated area in each region, agricultural irrigation water use efficiency can affect agricultural carbon emissions and output efficiency by changing inter-regional agricultural production costs and intra-agricultural production structure (Xu et al, 2022); 7) farmland operation scale differences (SC) is expressed by the per capita crop sown area, it has been proven that the scale of agricultural production leads to differences in the cost of adoption of agricultural technology, and that larger scale of operation makes it easier to obtain economies of scale and adopt advanced technology (Helfand and Taylor, 2021;Mao et al, 2021); 8) financial support differences (IN) is expressed by the proportion of local financial expenditure on agriculture, many scholars have found that financial support for agriculture significantly affects agricultural carbon emissions (Guo et al, 2022); 9) marketization level differences (MA) is expressed by the marketization index measurements, according to (Fan et al, 2011). The level of marketization determines the flow and allocation of production factors and therefore has an impact on the spatial association network .…”
Section: Analysis Of Driving Factors Of Spatial Association Network O...mentioning
confidence: 99%
“…The essence of the urbanization process is a multidimensional transmutation process accompanied by the flow of capital, labor, technology, and other factors from the countryside to the city, and the reconfiguration of factors between urban and rural areas, which has a great impact on the production scale and cultivation structure of agriculture (Tian et al, 2016;Xiong et al, 2020;Joséf, 2022); 4) rural labor education level differences (ED) is expressed by the average years of education of rural residents. The labor force is the decision maker of agricultural production methods and its level of education has a significant impact on the adoption and application of pioneering technologies (Wang et al, 2019;Wu et al, 2021;Khanh and Nguyen, 2022); 5) financial development level differences (FI) is expressed by the ratio of deposit and loan balance of financial institutions to GDP, a sound financial service system can provide financial support for agricultural transformation and upgrading and green technology progress (Huang et al, 2014;Cao et al, 2022;Gao et al, 2022); 6) agricultural irrigation water utilization rate differences (WA) is expressed by the ratio of effective irrigated area to cultivated area in each region, agricultural irrigation water use efficiency can affect agricultural carbon emissions and output efficiency by changing inter-regional agricultural production costs and intra-agricultural production structure (Xu et al, 2022); 7) farmland operation scale differences (SC) is expressed by the per capita crop sown area, it has been proven that the scale of agricultural production leads to differences in the cost of adoption of agricultural technology, and that larger scale of operation makes it easier to obtain economies of scale and adopt advanced technology (Helfand and Taylor, 2021;Mao et al, 2021); 8) financial support differences (IN) is expressed by the proportion of local financial expenditure on agriculture, many scholars have found that financial support for agriculture significantly affects agricultural carbon emissions (Guo et al, 2022); 9) marketization level differences (MA) is expressed by the marketization index measurements, according to (Fan et al, 2011). The level of marketization determines the flow and allocation of production factors and therefore has an impact on the spatial association network .…”
Section: Analysis Of Driving Factors Of Spatial Association Network O...mentioning
confidence: 99%
“…Studies have shown that FDI (Foreign direct investment) in agriculture has a positive impact on the intensity of CO2 equivalent emissions in developing countries (Kastratović 2019). Studies have shown that agricultural financial support and fertiliser use have a significant impact on carbon emissions from agricultural production in China Guo et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural activity is one sector that contributes to the production of GHG emissions into the atmosphere such as methane (CH 4 ), nitrogen dioxide (NO 2 ), and also carbon dioxide (CO 2 ) [1,2,3,4,5]. Carbon dioxide is produced from decomposition by microbes and burning dead organic matter such as twigs and pruned leaves which can be used as fertilizer [6,7,8].…”
Section: Introductionmentioning
confidence: 99%